Islamic Faith Belief and Infodemic Toward Society's Compliance With Covid-19 Health Protocols - Sitti Raodhah; Azman Arsyad (Al-Sihah : The Public Health Science Journal, 2023)
The implementation of health protocols during Covid-19 pandemic is very important to the prevention of virus transmission, but it had not been implemented optimally. Therefore, this study aimed to analyze the contribution of provisions in Islamic teachings and Infodemic to compliance with health protocols. The quantitative method was adopted with an observational study approach involving a total of 421 people. This sample was selected using the criteria of being Muslim, at least 18 years old, and willing to fill out a questionnaire online using the Google form. The results showed that the contribution of Islamic teachings in the form of Qada and Qadr belief and Covid-19 Infodemic had a positive effect on compliance with implementing the health protocols. Furthermore, the contribution of belief in Islamic teachings and Covid-19 Infodemic had a simultaneous positive effect on compliance with implementing health protocols. This study proved that religious and spiritual approaches can effectively increase community compliance in adhering to public health efforts.